Study on the Effect of Jet Position and Size on Heat Transfer in a Small Containment - Xiong, Wang; Fang, Yuan; Lin, Shengsheng; Wang, Shengfei (Frontiers in Energy Research, 2022)
In the event of Main Steam Line Break accident (MSLB), the rise of temperature and pressure threatens the integrity of the containment, which caused by a large amount of mixed gas injects into the containment rapidly. Due to the structural difference between small and large containment, it is necessary to study the heat transfer in the complex space of the small containment. Based on research method which is from simple to complex, in this paper, a serious of experiments and numerical simulations are carried out with different jet positions and sizes using hot air without phase change as the working medium. The results show that, the temperature field above the jet is complex and affected by many factors such as buoyancy, the initial kinetic energy, internal structure, etc.. When the jet flow rate is constant, the smaller the jet size is, the faster the velocity is, which results in a large circulation and stronger heat exchange with the wall of containment. This causes that the temperature above the jet is lower than the large jet size condition and the temperature below the jet is slightly higher. The jet position mainly affects relative position with the complex space in the containment. When the jet is located in a narrow space, the overall temperature in the containment is higher than the jet located in a large space. In addition, when it is close to the obstacle, the core region of the jet will shift slightly towards the obstacle.